The efficacy of steroids in reducing morbidity and mortality from extreme hyperthermia and heatstroke-A systematic review - Edward Walter; Oliver R. Gibson (Wiley, 2020)
Abstract Severe hyperthermia from classical or exertional heatstroke, or from drug ingestion or other noninfective pyrogens, is associated with a high mortality and morbidity. A systemic pro‐inflammatory response occurs during heatstroke, characterized by elevated cytokines with endotoxemia from elevated lipopolysaccharide (LPS) levels. Corticosteroids reduce LPS and cytokine levels, suggesting that they may improve outcome. A systematic review searching Embase, MEDLINE, and PubMed from the earliest date available until September 2019 was conducted, according to the PRISMA guidelines, with five papers identified. In four studies, systemic steroids administered before or at the onset of heat stress improved mortality or reduced organ dysfunction. Survival time was greatest when steroid administration preceded heat stress. In one study, a nonsignificant increase in mortality was seen. A dose response was observed, with higher doses extending survival time. Animal studies suggest that steroids improve mortality and/or organ dysfunction after an episode of heat stress or extreme hyperthermia.